Morality and Freedom: a critical investigation of the relatedness of morality and freedom, and its significance for the moral justification of the practice of biomedical moral enhancement - Mantovani, Beatrice S. A. (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.